Kedudukan Korporasi sebagai Subjek Hukum Pidana dalam Tindak Pidana Pelanggaran Hak Asasi Manusia: Tinjauan terhadap KUHP dan Peraturan Perundang-Undangan Terkait - Mhd. Hasbi; Muhammad Dhobit Azhary Lubis; Annisa Danti Avrilia Ningrum; Surya Hamdani (AKADEMIK: Jurnal Mahasiswa Humanis, 2026)
This study examines the unresolved legal gap concerning the status of corporations as subjects of criminal law in cases of human rights violations. Although the 2023 Indonesian Criminal Code explicitly recognizes corporations as criminally liable entities through the application of identification theory and corporate culture theory, the Human Rights Court Law still limits liability to individual perpetrators. This disharmony creates uncertainty and weakens efforts to address corporate involvement in serious human rights violations, particularly in cases involving systemic abuses, environmental destruction, and labor exploitation. The objective of this research is to analyze the juridical position of corporations under the 2023 Criminal Code and evaluate the extent to which existing legislation supports or fails to support the enforcement of corporate criminal liability in human rights violations. Using a normative juridical method, this study examines statutory provisions, legal principles, and relevant international instruments, including the United Nations Guiding Principles on Business and Human Rights. The findings show that the 2023 Criminal Code provides a more comprehensive framework for imposing corporate liability, including expanded forms of sanctions and clearer attribution standards. However, the absence of corporate liability provisions in the Human Rights Court Law presents a substantive obstacle to consistent law enforcement. The study concludes that legislative harmonization, strengthened institutional capacity, and the development of specialized procedural mechanisms are essential to ensure accountability for corporations implicated in human rights violations.